Fluoride kinetics in saliva after the use of a fluoride-containing chewing gum - Bijella, Maria Francisca Thereza Borro (2005)
There is a relationship between the use of fluoride, the reduction of dental caries and the increase of dental fluorosis. The purpose of this study was to analyze the fluoride kinetics in saliva after using the HappydentTM chewing gum, which contains 3.38 mg of fluoride as monofluorophosphate. Fifteen 7-9-year-old volunteers were instructed to chew the gum TridentTM (control) and HappydentTM on different days. Total saliva was collected for 3 minutes, at 0, 3, 6, 9, 15, 30 and 45 minutes after starting chewing. Salivary fluoride was analyzed with a fluoride-specific electrode (Orion 96-09) after acid hydrolysis. The data were analyzed by two-way analysis of variance and by Tukey’s post hoc test (p < 0.05). The mean amounts ± sd (mg) of fluoride released in saliva were 0.276 ± 0.126 and 0.024 ± 0.014 for HappydentTM and TridentTM respectively. The fluoride amount in the saliva samples after the use of Happydent was significantly higher than after the use of TridentTM in all experimental periods, except after 30 and 45 minutes. The high fluoride presence in saliva after the use of Happydent may be significant to prevent dental caries and this should be evaluated in clinical researches. On the other hand, children at an age of risk for dental fluorosis should avoid the use of HappydentTM.